Implementasi Simple Service Discovery Protocol (SSDP) untuk Pencarian Layanan pada Wi-Fi Direct Berbasis Android - Redila Permata Anindita; Eko Sakti Pramukantoro; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Over the past years, the use of wireless technologies has been increased and has changed how the electronic devices interact and communicate. Wi-Fi Direct is one of wireless technologies exist. Wi-Fi is the development of Wi-Fi Alliance by utilizing Peer-to-Peer infrastructure. The purpose of Wi-Fi Direct technology is to improve device-to-device communication directly with Wi-Fi. On a Wi-Fi Direct network, a service discovery algorithm is needed to help them share their services. This study aims to implement the service discovery algortihm on one group of Wi-Fi Direct with the Simple Service Discovery Protocol (SSDP) algorithm and test performance of the system. Performance testing experiments of this study to determine the delay of some process that is done, in the process of peer discovery, forming group, and service discovery with SSDP. The result of impementation SSDP algorithm on one group of Wi-Fi Direct can be concluded that a Group Owner can share the service to its clients and based on the performance testing obtained result for the fastest delay of peer discover process is 10,328 seconds and the longest delay of peer discovery is 19.914 seconds, for delay of the group formation process the fastest delay of 0.305 seconds and the longest delay of 0.633 seconds, for service discovery process with SSDP delayed fastest in 0.035 seconds and the longest delay in 0.065 seconds.